Pengaruh Strategi Koping terhadap Intensi Kambuh pada Penyalahguna Narkoba: Peran Moderasi Sikap, Norma dan Kontrol Perilaku - Rahmi Lubis; Vitari Fahlika (Journal Psikologi Forensik Indonesia, 2024)
Drug abuse is an unlawful act that causes detrimental effects. Abusers need rehabilitation to overcome these effects and prevent relapse. However, rehabilitation programs do not guarantee that individuals will completely stop abusing drugs. One of the factors that influences the intention to relapse is coping strategies. On the other hand, attitudes, norms, and behavioral control regarding drug abuse determine the relapse intention. This research examines the role of attitudes, norms, and behavioral control in assessing the influence of coping strategies on relapse intentions. A total of 60 residents who had relapsed at least once and were undergoing rehabilitation for at least 2 months at the North Sumatra BNN were involved in this research. The research tools are coping strategies and relapse intention scales, tested for validity and reliability. Research data was analyzed using a moderation test with Jamovi software version 2.0. The results show that coping strategies does not influence relapse intentions directly. Attitudes towards drug abuse, subjective norms, and behavioral control significantly increase the negative influence of coping strategies on relapse intentions. Residents who believe drugs are detrimental, feel the environment prohibits abusing them, believe there is little chance of abusing them, and have adaptive coping skills will have a low intention to relapse. The results are advantageous in relapse prevention programs for abusers so that they focus more on cultivating attitudes, norms, and self-efficacy that support abstinence decisions